A novel compound, SYHA1813, inhibits malignant meningioma growth directly by boosting p53 pathway activation and impairing DNA repair - Lan, Yanjie; Li, Shenglan; Wang, Jiachen; Yang, Xin; Wang, Can; Huang, Mengqian; Zhang, Rong; Chen, Feng; Li, Wenbin (Frontiers in Oncology, 2025)
IntroductionMeningioma is a common tumor of the central nervous system but effective therapies for malignant meningiomas are still lacking. Therefore, the development of novel therapeutic reagents is urgently needed. SYHA1813 is a novel compound and our previous study demonstrated its potent anti-tumor activity on glioblastoma through the inhibition of macrophages and human umbilical vein endothelial cells (HUVECs). However, the precise functional role of SYHA1813 in meningiomas remains unclear.MethodWe aimed to investigate the direct tumor-inhibitory effects of SYHA1813 on meningioma both in vitro and in vivo, and explore its potential molecular mechanisms.ResultsOur results showed that SYHA1813 suppressed the proliferation, colony formation, migration, and invasion of meningioma cells in vitro. Furthermore, we found SYHA1813 induced G2/M cell cycle arrest, apoptosis, and cellular senescence. Mechanistically, RNA-seq revealed that SYHA1813 activated the P53 pathway and impaired DNA repair. In vivo, SYHA1813 effectively inhibited the growth of meningioma xenografts in a mouse model. Additionally, in an ongoing first-inhuman phase I trial, this patient with recurrent meningioma provided preliminary clinical evidence supporting the anti-tumor activity of SYHA1813.DiscussionThis study unveiled a novel antitumor mechanism of SYHA1813, showing its ability to directly target and kill meningioma cells in vitro and in vivo. Our findings highlighted the promising potential of SYHA1813 as a therapeutic agent for treating malignant meningiomas.